Business principles and management - Burrow, Jim (Thomson South-Western, 2008)
Introduce your students to today's critical business management concepts and principles in a realistic, investigative, and enriching manner with Business Principles and Management. Explore the global dimension of business and possible career opportunities and bring the world of business to the classroom. Business Principles and Management combines fundamental concepts with a strong lesson-based instructional design, weaving in research opportunities, creative methods of assessment, interesting real-world features, mathematical calculations, case studies, and academic connections. - Back cover